Konstribusi Buruh Wanita Pembersih Ikan Terhadap Pendapatan Keluarga di Desa Kuala Bubon, Kecamatan Samatiga, Kabupaten Aceh Barat - Keumala Fadhiela ND; Ade Masyita (Universitas Batangahari Jambi, 2022)
Abstract. The study aims to analyze the contribution of female workers to the formation of family income, study the socioeconomics of female workers, and analyze the relationship between variables: age, education level, number of hours worked, number of dependents or people who depend on the income of female working families. The data collection method uses descriptive analysis and through observation with female fish janitors in Kuala Bubon Village with the help of questionnaires that have been compiled before. As for the results of the research obtained from the study, that the total income of women fish farmers in Kuala Bubon Village amounted to Rp.1.040.000 monthly and the total income of respondents' families amounted to Rp.9.497.333monthly, resulting in the contribution of respondents' income to family income by 10%.